(untitled) (The Pakistan Development Review, 1981)
A number of social and economic indices are constructed by utilising a total of 120 variables to compare Pakistan with 96 other developing countries of Asia, Africa and Latin America. These countries are ranked on scales of these indices by using the Wroclaw Taxonomic Method and are grouped on the basis of similarities with the help of a clustering technique. Pakistan seems to have achieved a reasonable degree of success in both social and economic areas but her performance in the latter is more pronounced.